USM RECEIVES 4 DIALYSIS MACHINES AND 2 REVERSE OSMOSIS MACHINES FROM 1MDB FOUNDATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, January 2015 Universiti Sains Malaysia (USM) recently received four dialysis machines and two reverse osmosis machines worth RM250,000 from 1Malaysia Development Berhad (1MDB) Foundation. The machines were handed over by 1MDB Foundation Social Corporate Responsibility Director Dato’ Dr. Shamsul Anuar Sulaiman to USM ViceChancellor Profesor Dato’ Dr. Omar Osman in a simple handover ceremony at Hospital USM (HUSM).